Influence of preformed donor-specific antibodies and C4d on early liver allograft function. (December 2013) - Perera, MT; Silva, MA; Murphy, N; Briggs, D; Mirza, DF; Neil, DAH
Abstract Introduction. The impact of preformed donor-specific antibodies (DSA) is incompletely understood in liver transplantation. The incidence and impact of preformed DSA on early post liver transplant were assessed and these were correlated with compliment fragment C4d on allograft biopsy. Methods. Pretransplant serum from 41 consecutive liver transplant recipients (brain dead donors; DBD = 27 and cardiac death donors; DCD = 14) were tested for class-specific anti-human leukocyte antigen (HLA) and compared against donor HLA types. Liver biopsies were taken during cold storage (t-1) and post-reperfusion (t0) stained with C4d and graded for preservation-reperfusion injury (PRI). Results. Of the 41 recipients, 8 (20%) had anti-HLA class I/II antibodies pretransplant, 3 (7%) were confirmed preformed DSA; classes I and II (n=1) and class I only (n=2). No biopsies showed definite evidence of antibody-mediated rejection. Graft biopsies in overall showed only mild PRI with ischemic hepatocyte C4d pattern similar in both positive and negative DSA patients. One DSA-positive (33%) compared with four DSA-negative patients (10%) had significant early graft dysfunction; severe PRI causing graft loss from primary nonfunction was seen only in DSA-negative group. Allograft biopsy of preformed DSA-positive patient demonstrated only minimal PRI; however, no identifiable cause could be attributed to graft dysfunction other than preformed DSA. Conclusion. Preformed DSA are present in 5–10% liver transplant recipients. There is no association between anti-HLA DSA and PRI and C4d, but preformed DSA may cause early morbidity. Larger studies on the impact of DSA with optimization of C4d techniques are required.